Prevalence of vaginitis in different age groups among females in Greece. (18th August 2017) - Sianou, Argiri; Galyfos, George; Moragianni, Dimitra; Baka, Stavroula
Abstract: Patients with vaginitis were classified into four groups: Group A (prepubertal under-aged females); Group B (pubertal under-aged females); Group C (reproductive age adult females); Group D (postmenopausal adult females). All vaginal specimens underwent microscopy, amine testing, Gram staining and culturing. Overall, 163 patients were included (33, 14, 81 and 35 patients, respectively). The most common infection was bacterial vaginosis (BV), followed by Ureaplasma infection, aerobic vaginitis (AV) and candidiasis. The most common AV-associated organism was Escherichia coli and the most common BV-associated organism was Gardnerella vaginalis . AV was more frequent in Group A, BV in Group C and Ureaplasma infections in Groups C/D. Decreased lactobacilli concentrations were associated with BV in fertile patients (Groups B–C). Although presentation of vaginitis is similar among females of different age in Greece, type and prevalence of pathogens differ. Normal vaginal flora changes are associated with higher risk of vaginitis in specific age groups. Impact Statement: The worldwide incidence of reproductive tract infections has been increasing, with specific pathogens being associated with significant risk of morbidity and complications. However, literature data on the distribution of such infections in different age groups is limited. Therefore, the aim of this study was to provide data on the prevalence and causes of vaginitis in adult and non-adult females of all ages. This study has shown that although presentation of vaginitis is similar among females of different age groups and menstrual status in Greece, type and prevalence of responsible pathogens are different among groups. Changes in normal vaginal flora seem to be associated with higher risk of vaginitis in specific age-groups as well. These findings could contribute in adjusting diagnostic and therapeutic strategies for each age group according to the prevailing pathogens. Further research on antibiotic resistance and treatment outcomes for each age group should be conducted.